Productive efficiency and ownership when market restructuring affects production technologies - Astrid Cullmann; Maria Nieswand; Julia Rechlitz (Deutsches Institut für Wirtschaftsforschung (DIW), 2017)
While the link between the ownership and productive efficiency of firms has been discussed extensively, no consensus exists regarding the superiority of one or the other in non-competitive, regulated environments. This paper applies a flexible production model to test for efficiency differences associated with ownership types while allowing the production to adapt to market restructuring over time. Our empirical setting is based on a new, rich micro dataset of electricity distribution firms operating between 2006 and 2012 in Germany, where the energy transition enforces the adjustment of energy infrastructure. First, our results show that electricity distribution system operators adapted their production technologies over time. Second, there is no empirical evidence that public firms operated any less efficiently than private firms. The empirical findings are relevant to the (re)municipalization debate, which appears to have exaggerated the dichotomy between public and private utilities' efficiency
Keywords: L94; L51; L98; 330; Utilities; Ownership; Productivity; Electricity Distribution; Energiewende